(untitled) (Research, Society and Development, 2024)
The objective of this research is to analyze the rheumatic manifestations associated with arboviruses and their impacts on quality of life, exploring how these conditions affect the physical, mental and social functionality of patients, as well as the clinical and social implications resulting from such manifestations.. The review was carried out in six stages: 1) Identification of the theme and formulation of the guiding question; 2) Establishment of inclusion and exclusion criteria; 3) Search in databases such as PubMed, Scielo and BVS, considering publications between 2019 and 2024; 4) Selection and categorization of studies; 5) Extraction and analysis of data; 6) Synthesis and presentation of results. Arboviruses present variable rheumatological manifestations. CHIKV stood out for the chronicity of complications such as polyarthralgia and joint stiffness. Zika and dengue have self-limiting joint symptoms. It was observed that these conditions impact not only the physical, mental and social aspects, intensified by adverse socioeconomic conditions. It was concluded that arboviruses affect functionality and quality of life, with significant physical, emotional and social implications. The study reinforces the need for multidimensional management strategies, including rehabilitation, psychological support and health policies that prioritize the full recovery of patients, especially in endemic areas. The lack of longitudinal studies was highlighted, with emphasis on the urgency of increasing understanding of the long-term effects of these arboviruses.